Implantação de um programa de uso racional de água na universidade federal de goiás estudo de caso edifício da reitoria - GOMES, Marcelus Isaac Lemos (2011)
The water scarcity has led to changes in position of economic environmental and political issues besides trying to seek new sources of water located at further distances in places more distant. That is to reduce the amount of water needed by, urban population without compromising the quality of activities. This work had the objective to establish a water conservation program, initiated by the implementation of programs for the Rational Use of Water in the building of the Rectory of the Federal University of Goiás, in the city of Goiania. The building selected for the development of a Case Study is used for administrative activities. It comprises two floors, with total built up area of 2,013.84 m2, which was chosen because it showed characteristics that allowed the installation of water meter, for monitoring the daily consumption, and the registration of all points of water consumption, as well as the classification of user categories (including fixed and transitory people). The methodology used considered initially an evaluation and a diagnostic of the building selected for the study. In the sequence a plan was developed and the proposed actions to help in the reduction in water usage was later implemented. Finally, the management of the actions to keep rational usage of water took place including daily monitoring. Based on the analysis of the collected data an economic analysis was carry out to quantify the economic benefits achieved. The consumption data were collected over a period of 240 days, including 120 days before and 120 days after the implementation of water saving measures. The collected data allowed an analysis of the potential for reducing the monthly consumption of water, which in this case was around 30%. The economic analysis showed that the amount invested, including equipment and manpower, would be paid in approximately 20 months, considering average rate of the capital return equal to 0.75% per month.